Menilik Upah Minimum dan Ketimpangan Pendapatan di Indonesia - Rastri Paramita (Pusat Kajian Anggaran, 2021)
This study aims to determine the condition of the minimum wage, employment structure, and income inequality in Indonesia. The research method used is qualitative and sourced from secondary data obtained from BPS, laws, and regulations, policy briefs related to minimum wages and income gaps as well as the results of previous research. The results of this study in the form of a minimum wage will be effective if the structure of the workforce in a country is more dominant in working in the formal sector. In addition, the minimum wage that increases every year can reflect inflation due to rising prices of goods, causing real wages to tend to decline.In addition, the determination of minimum wages in each Province and Regency/City is still too simple because it has not taken into account the differences in regions, sectors, and types of businesses that exist in each region. The absence of detailed data related to economic and sociocultural data has caused the minimum wage setting policies implemented to date have not been able to reduce income inequality in Indonesia. Improvements in worker productivity must begin through improving worker education and skills.